DIAGNOSTIC VALUE OF CA-125 IN PATIENTS WITH EPITHELIAL OVARIAN CANCER AT THE DR. SOETOMO GENERAL HOSPITAL SURABAYA IN 2016 - Kintan Putri; Betty Agustina Tambunan; Willy Sandhika (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Ovarian cancer is the fourth cancer with most incidence in Indonesian female with 10.238 cases in 20141. Tumor marker CA-125 is assosciated with ovarian cancer, importantly epithelial ovarian cancer. This study aims to find out diagnostic value (sensitivity, specificity, positive predictive value, negative predictive value) of CA-125 among patients with epithelial ovarian cancer in Dr. Soetomo General Hospital Surabaya in 2016. This study used analytic cross sectional method and was performed by evaluating medical records of patients suspected for ovarian malignancy in Dr. Soetomo General Hospital Surabaya in 2016. There were total 97 patients found fit for criteria of inclusion in this study. Tissue histopathological examination confirmed 66 patients have epithelial ovarian malignancy and 31 patients do not. Samples distributed using 35 U/ml as CA-125 upper limit, TP: 54.64%, FP: 19.59%, FN: 13.40%, dan TN: 12.37%. Diagnostic value obtained as follows: sensitivity 80.30%, spesificity 38.71%, positive predictive value 73.61%, negative predictive value 48%, and accuracy 67.01%. Tumor marker associated with ovarian cancer CA-125 has found high in sensitivity but low in specificity among patients with epithelial ovarian cancer in Dr. Soetomo General Hospital Surabaya in 2016.